Production of Ethanol Using Yeast Isolates on Water Hyacinth and Azolla - Hossain, Riajul; Chowdhury, Miraj Kobad; Yeasmin, Sabina; Hoq, M Mozammel (Bangladesh Journal of Microbiology, 2011)
Fossil fuel depletion and limitations turn scientists to develop alternative fuels as well as biofuels. Cheap cellulosic biomass could be used as raw materials for production of ethanol. Water hyacinth (Eichhornia crassipes) and Azolla (Azolla pinnata) are the two biomass resources considered in this study. The purpose of this study was to produce ethanol using water hyacinth and Azolla as substrates used to produce ethanol by using two yeasts presumptively identified as Sachharomyces cerevisiae (Sc-SR4, Sc-MR8) and Kluyveromyces marxianus (Km-SR3). For saccharification, water hyacinth and Azolla were pretreated with different concentrations (0.25 to 1.0%) of sulphuric acid. D-glucose and reducing sugar yield was found higher for Azolla (40% of dry weight) than water hyacinth (25.2% of dry weight). The ethanol yield was higher with water hyacinth, (0.32g/g ethanol), than that of Azolla, (0.20g/g ethanol). Acid and heat treatment both affected saccharification. The water hyacinth hydrolysate fermentation resulted in 1.9% (v/v) ethanol by the isolate Sc-SR4 and 1.4% (v/v) ethanol by the Sc-MR8 and thus the Sc-SR4 proved to be more efficient than Sc-MR8. Similarly, fermentation of Azolla hydrolysate gave 1.01% (v/ v) ethanol by Sc-SR4 and 0.45% (v/v) by the Sc-MR8 isolate. Key words: Biofuel; Ethanol; Yeast; Cellulosic Substrates DOI: http://dx.doi.org/10.3329/bjm.v27i2.9173 BJM 2010; 27(2): 56-60